The moderating effect of virtual leadership behaviors towards knowledge sharing in online programming communities - Shahatha, Abdulrazak F.; Ahmad, Rahayu (2018)
Although there is a significant growth of emerging online programming communities, little succeeded in encouraging members to contribute and share their knowledge. Addressing problems of low contribution trigger researchers to examine the role of leadership in virtual communities. This study grounded on path-goal theory, examines the role of participative leadership and achievement oriented leadership behaviour toward knowledge sharing in online programming community. This proposed model is tested empirically using data collected from 20 online programming communities. The result from the structural equation modelling suggests that outcome expectancy and self-efficacy influences knowledge sharing behaviour of members in online programming community. The finding implied that although online communities are informal in nature, the appropriate type of leadership can boost the members’ efficacy and outcome expectancy to participate in knowledge sharing. Ideally, with the appropriate level of autonomy and recognition of members contributions can motivate members to continuously contribute to online programming communities and promoting the sustainability in this platform.